Increasing consultant-level staffing as a proportion of overall physician coverage improves emergency department length of stay targets - Dominic Jenkins (9983446) (2021)
Objectives One goal of Emergency Department (ED) operations is achieving an overall length of stay (LOS) that is less than four hours. The goal of the current study was to assess for association between increasing number of on-duty EM Consultants and LOS, while adjusting for overall (all-grade) on-duty emergency doctors’ numbers and other operational factors. Methods This was a retrospective analysis of three years (2016–2019) of data, employing a unit of analysis of 3276 eight-hour ED shifts. The study was conducted using a prospectively populated ED database in a busy (annual census 420,000) Middle Eastern ED with staffing by Consultants and multiple non-Consultant grades (Specialists, fellows, and residents). Using logistic regression, the main predictor variable of “on-duty Consultant n” was assessed for association with the study’s primary (dichotomous) endpoint: whether a shift’s median LOS met the target of < 240 min. Linear regression was used to assess for association between on-duty Consultant n and the study’s secondary (continuous) endpoint: median LOS for the ED shift. Results Multivariate logistic regression adjusting for a number of operations factors (including total EP on-duty complement) identified an association between increasing n of on-duty Consultants and the likelihood of a shift’s meeting the 4-h ED LOS target (OR 1.27, 95% CI 1.20 to 1.34, p < .0001). Multiple linear regression, which also adjusted for total on-duty EP n and other operational factors, also indicated LOS benefit from more on-duty Consultants: each additional on-duty Consultant was associated with a shift’s median LOS improving by 5.4 min (95% CI 4.3 to 6.5, p < .0001). Conclusions At the study site, in models that adjusted for overall on-duty EP numbers as well as myriad other operational factors, increasing numbers of on-duty Consultants was associated with a statistically and operationally significant reduction in ED LOS. Other Information Published in: BMC Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s12873-020-00399-8